Identifikasi Interaksi Obat pada Resep dengan Diagnosa Gangguan Sistem Endokrin Periode Bulan Juli 2024 di Rumah Sakit X Kota Bandung - Salma Tri Octaviany; Tina Rostinawati (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Drug interactions can occur when drugs are administered simultaneously with other drugs, both pharmacologically and clinically. This study aims to identify drug interactions that occur in prescriptions with patients experiencing endocrine system disorders for the period July 2024 at Hospital X, Bandung City. Endocrine disorders, involving hormonal dysfunction such as that of the thyroid, adrenals, or pancreas, can affect the pharmacokinetics and pharmacodynamics of drugs, thereby increasing the risk of interactions. This research method involved randomly collecting two prescriptions per day, with a total of 60 recipes analyzed. The results of the assessment showed that there were 15 potential drug interactions with a percentage of 25%, consisting of one minor interaction (6.67%), 15 moderate interactions (93.33%), and no major interactions were found.